Perovskite quantum dot glue as well as preparation method and application thereof

By combining multi-dentate thiol compounds with perovskite quantum dots and resins, the problem of insufficient resistance to blue light and dry heat aging by perovskite quantum dots is solved, and the stability and optical performance are achieved. Improve, simplify the process and reduce costs, and is suitable for industrial production.

CN119161843APending Publication Date: 2024-12-20WUXI UTMOST LIGHT TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310735069.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing perovskite quantum dispenser has shortcomings in its blue light resistance and dry heat resistance, and the preparation process is complex and costly, making it not suitable for industrial production.

Method used

Multidentate thiol compounds are used as multifunctional ligands to combine with perovskite quantum dots and resins, polymer monomers and other components. Through coordination and cross-linking reactions, the surface defects of quantum dots are reduced and the stability of glue is improved. and optical properties.

Benefits of technology

It significantly improves the stability and blue light resistance and dry heat aging resistance of perovskite quantum dispenser, simplifies the preparation process, reduces costs, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161843A_ABST
    Figure CN119161843A_ABST
Patent Text Reader

Abstract

The invention provides perovskite quantum dot glue as well as a preparation method and application thereof. The perovskite quantum dot glue comprises resin, perovskite quantum dots, a multifunctional ligand, a polymer monomer and an initiator, the multifunctional ligand is a polydentate sulfydryl compound. According to the perovskite quantum dot glue disclosed by the invention, the polydentate sulfydryl compound and other components are compounded and have a synergistic effect, so that the perovskite quantum dot glue is good in stability, good in blue light resistance and dry heat aging resistance and long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical films for displays, and in particular relates to a perovskite quantum dot glue and a preparation method and application thereof. Background Art

[0002] As people's living standards continue to improve, the requirements for display technology are also getting higher and higher. For this reason, quantum dot display technology has emerged. Among them, perovskite quantum dots have attracted widespread attention as an advanced semiconductor optoelectronic material. Perovskite quantum dots with a molecular formula of ABX3 (where A is Cs, FA, MA, etc., B is Pb, Sn, etc., and X is any one of Cl, Br, and I) have triggered a research boom due to their excellent optical properties, such as easy adjustment of emission wavelength, high color purity, wide color gamut, high defect tolerance, and high photoluminescence quantum yield, etc., and can be applied in a variety of optoelectronic device fields. Especially in the display field, perovskite quantum dots have unique advantages over traditional cadmium quantum dots: First, their synthesis and preparation time is shorter than that of cadmium-based quantum dots. Compared with the traditional cadmium-based quantum dot preparation method, perovskite quantum dots do not require the construction of a core-shell structure, and the process is simpler and more suitable for industrial development; Second, the emission peak half-width of perovskite quantum dots is narrower than that of traditional cadmium-based quantum dots, and the covered color gamut is higher than that of cadmium-based quantum dots; Third, perovskite quantum dots can easily pass the mandatory standard ROHS certification established by EU legislation that traditional cadmium-based quantum dots cannot pass, showing better application prospects.

[0003] The most common application form of perovskite quantum dots in the display field is to use different types of glue and combine them with water and oxygen barrier films to prepare optical films, which are finally used in display modules. Therefore, it is particularly important to prepare high-performance and stable perovskite quantum dot glue. The degree of compatibility between perovskite quantum dots and glue will change accordingly with different glue formulas. This degree of compatibility will not only affect the initial performance of the perovskite quantum dot optical film, but also the stability of the film. For this reason, researchers have rationally optimized the glue components.

[0004] For example, CN114311864A discloses a perovskite quantum dot glue, including a photocurable resin, a diluent monomer, etc.; however, the components selected by the perovskite quantum dot glue, such as isobornyl methacrylate, polyurethane resin, etc., can only simply encapsulate the perovskite quantum dots from a physical perspective, but cannot reduce the surface defects of the perovskite quantum dots from a chemical perspective, and thus cannot improve its dry heat or blue light stability.

[0005] For example, CN111410748A discloses a perovskite quantum dot composition and a preparation method thereof, a perovskite quantum dot film and a preparation method thereof. The different resins and monomers selected in the preparation of the perovskite quantum dot polymer film only play a simple physical packaging role for the quantum dots themselves during the curing process, and perform poorly in passivating the quantum dots.

[0006] The common defects of the existing technology are: perovskite quantum dots have many surface defects and average optical properties. After mixing with glue, they will experience varying degrees of efficiency reduction or quenching and other undesirable phenomena; the existing passivation strategy has many steps, is time-consuming and costly, which is not conducive to scale and even less to industrial production; even if the stability of perovskite quantum dots can be temporarily improved, the blue light resistance and dry heat aging resistance of the perovskite quantum dot glue obtained after mixing with glue still need to be further improved, and its stability is far from practical application.

[0007] Therefore, developing a perovskite quantum dot glue with fewer surface defects, good stability, resistance to blue light, and good resistance to dry heat aging is an urgent problem to be solved in this field. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a perovskite quantum dot glue and a preparation method and application thereof; in the perovskite quantum dot glue, the perovskite quantum dots have few surface defects, the glue has stable performance, good blue light resistance and dry heat aging resistance, and the preparation method is simple, which is more conducive to industrial scale-up production.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a perovskite quantum dot glue, which comprises a resin, perovskite quantum dots, a multifunctional ligand, a polymer monomer and an initiator; the multifunctional ligand is a multidentate thiol compound.

[0011] In the present invention, the multidentate thiol compound, on the one hand, can coordinate with the perovskite quantum dots to play a passivation role, reduce the surface defects of the perovskite quantum dots, and improve the important optical properties of the quantum dots such as the photoluminescence quantum yield and half-peak width; on the other hand, the multidentate thiol compound plays the role of a monomer and promotes initiation, that is, it can replace part of the monomer and the initiator, participate in the cross-linking reaction, improve the cross-linking degree and curing degree of the perovskite quantum dot glue, and further improve the stability of the glue; by compounding the multidentate thiol compound with other components, synergistically enhancing the effect, the perovskite quantum dot glue has good stability, good blue light resistance and dry heat aging resistance, and a long service life.

[0012] Preferably, the multidentate thiol compound includes any one of trimethylolpropane tris(3-mercaptopropionate), 3-mercaptopropionic acid-[2,4,6-trioxo-1,3,5-triazine-1,3,5(2H,4H,6H)-secondary]tri-2,1-ethylene glycol ester, tetrakis(3-mercaptopropionic acid) pentaerythritol ester, tetrakis(3-mercaptobutyric acid) pentaerythritol ester or 1,4-bis(3-mercaptobutyryloxy)butane; more preferably trimethylolpropane tris(3-mercaptopropionate).

[0013] Preferably, the mass ratio of the perovskite quantum dots to the multifunctional ligand is 1:(0.1-10), wherein the specific value in (0.1-10) can be, for example, 0.1, 0.2, 0.3, 0.4, 0.6, 0.8, 1, 1.2, 1.6, 1.9, 2, 2.2, 2.5, 2.8, 3, 3.3, 3.5, 3.8, 4, 4.2, 4.3, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 5.9, 6, 6.2, 6.4, 6.6, 6.8, 7, 7.2, 7.4, 7.6, 7.8, 8, 8.1, 8.2, 8.5, 8.8, 9, 9.2, 9.4, 9.6, 9.8, 10, etc. It should be particularly noted that, in order to facilitate understanding and practical use, the relative contents of perovskite quantum dots and multifunctional ligands in the present invention are limited in the form of mass ratio. When the substances are determined, it is easy for those skilled in the art to convert the mass ratio into a molar ratio. For example, when the perovskite quantum dots are FAPbBr3 quantum dots (the molecular weight of FAPbBr3 is 491.98) and the multifunctional ligand is trimethylolpropane tris(3-mercaptopropionate) (the molecular weight of trimethylolpropane tris(3-mercaptopropionate) is 398.55), it can be calculated that the molar ratio corresponding to the mass ratio of 1:(0.1-10) is 1:(0.123-12.3), wherein the specific values ​​in (0.123-12.3) can be, for example, 0.123, 0.2, 0.4, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 12.3, etc.

[0014] In the present invention, if the mass ratio of the multifunctional ligand to the perovskite quantum dots is not within the above range, the ideal effect may not be obtained: if the amount of the multifunctional ligand is too small, the passivation effect on the surface of the perovskite quantum dots will be poor, affecting the stability of the quantum dot glue; if the amount is too large, it will affect the optical properties of the perovskite quantum dots and the stability of the glue.

[0015] Preferably, the molecular formula of the perovskite quantum dot is ABCl x Br y I 3-x-y; wherein A is selected from at least one of Cs, FA or MA; B is selected from Pb and / or Sn; 0≤x≤3, 0≤y≤3.

[0016] Preferably, the perovskite quantum dots include FAPbBr3 and / or CsPbBr3.

[0017] Preferably, the resin includes at least one of acrylic resin, polyurethane resin, epoxy resin, silicone resin, polyurethane acrylic resin, fluorosilicone modified polyurethane acrylate resin, epoxy acrylic resin or polyester resin, and more preferably polyurethane acrylic resin and / or fluorosilicone modified polyurethane acrylate resin.

[0018] Preferably, the polymer monomer is a compound containing a carbon-carbon double bond.

[0019] Preferably, the polymer monomers include propylene monomers and / or ethylene monomers.

[0020] Preferably, the polymer monomer includes at least one of isobornyl acrylate, lauryl acrylate, n-butyl methacrylate, isooctyl methacrylate, isobornyl methacrylate, isodecyl methacrylate, lauryl methacrylate, hexanediol dimethacrylate, hexanediol diacrylate, trimethylolpropane triacrylate or styrene.

[0021] Preferably, the initiator comprises a photoinitiator.

[0022] In the present invention, the photoinitiator includes but is not limited to α-hydroxyisobutyrophenone (photoinitiator 1173), diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO), photoinitiator TPO-L, photoinitiator 2959, and the like.

[0023] Preferably, the perovskite quantum dot glue also includes diffuse particles.

[0024] Preferably, the diffusion particles include organic silicon compounds and / or inorganic oxides.

[0025] In the present invention, the inorganic oxide includes but is not limited to at least one of silicon dioxide, titanium dioxide and zinc oxide.

[0026] As a preferred technical solution of the present invention, the perovskite quantum dot glue includes 10-40 parts of resin (for example, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, etc.), 0.1-0.3 parts of perovskite quantum dots (for example, 0.1 parts, 0.12 parts, 0.14 parts, 0.16 parts, 0.18 parts, 0.2 parts, 0.22 parts, 0.24 parts, 0.26 parts, 0.28 parts, 0.3 parts, etc.) ), 0.02-2 parts of multifunctional ligand (for example, 0.02 parts, 0.04 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.12 parts, 0.14 parts, 0.16 parts, 0.18 parts, 0.2 parts, 0.22 parts, 0.25 parts, 0.28 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts, 0.5 parts, 0.55 parts, 0.6 parts, 0.65 parts, 0.7 parts, 0.75 parts, 0.8 parts, 0.85 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts , 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts, etc.), polymer monomer 0.02-2 parts (for example, it can be 0.02 parts, 0.04 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.12 parts, 0.14 parts, 0.16 parts, 0.18 parts, 0.2 parts, 0.22 parts, 0.25 parts, 0.28 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts, 0.5 parts, 0.55 parts, 0.6 parts, 0.65 parts, 0.7 parts, 0.75 parts, 0.8 parts, 0.85 parts, 0.9 parts, 1 part, The invention relates to a kind of nanostructured carbon foam, which has the following advantages: the nanostructured carbon foam has the following advantages: 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts, etc.), 0.1-0.4 parts of initiator (for example, it can be 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, etc.) and 1-4 parts of diffusion particles (for example, it can be 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, etc.).

[0027] In the present invention, the components of the glue are within the above-defined range, and the types of the components are within the preferred range, the compatibility with the perovskite quantum dots is better, the glue performance is more stable, and the blue light resistance and dry heat aging resistance are better.

[0028] In a second aspect, the present invention provides a method for preparing the perovskite quantum dot glue according to the first aspect, the preparation method comprising:

[0029] The perovskite quantum dot glue comprises resin, perovskite quantum dots, multifunctional ligands, polymer monomers and initiators, so as to obtain the perovskite glue.

[0030] Preferably, the mixed material further comprises diffusion particles.

[0031] Preferably, the mixing time is 10 to 60 min, for example, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, etc.

[0032] In the present invention, the step of vacuum degassing is further included after the mixing; the degassing time is 1 to 10 minutes, for example, 1 minute, 2 minutes, 4 minutes, 6 minutes, 8 minutes, 10 minutes, etc.

[0033] In the present invention, during the mixing process of the multifunctional ligand with the perovskite quantum dots, the thiol group in the multifunctional ligand can form a strong coordination effect with lead and passivate the surface defects of the quantum dots; and in the subsequent preparation process of the optical film, through ultraviolet light curing, the thiol group in the multifunctional ligand and the olefin component in the glue achieve copolymerization growth through a click reaction, thereby improving the crosslinking degree of the quantum dot glue. In addition, the multifunctional ligand can also promote the initiation process, further improving the curing effect of the glue.

[0034] The route of the multifunctional ligand participating in the click reaction is as follows, illustratively:

[0035]

[0036] In a third aspect, the present invention provides a perovskite quantum dot optical film, wherein the perovskite quantum dot optical film comprises a base film and the perovskite quantum dot glue as described in the first aspect.

[0037] In the present invention, the base film comprises a water and oxygen barrier film.

[0038] In the present invention, there is no need to specifically limit the manufacturer and model of the water and oxygen barrier membrane. Water and oxygen barrier membranes from different manufacturers can achieve similar technical effects and have no impact on the effects of this application.

[0039] In a fourth aspect, the present invention provides a display module, comprising the perovskite quantum dot glue as described in the first aspect and / or the perovskite quantum dot optical film as described in the second aspect.

[0040] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The perovskite quantum dot glue provided by the present invention avoids the problems of conventional perovskite quantum dots having many surface defects and average optical properties. The addition of a multifunctional ligand effectively reduces the surface defects of the perovskite quantum dots and improves important optical properties of the quantum dots such as the photoluminescence quantum yield and half-peak width. At the same time, by compounding with other components such as resins and monomers, the crosslinking degree and curing degree of the glue are improved, and the stability of the glue is further improved. In addition, the multifunctional ligand has strong applicability, a simple preparation process, and low cost, and can realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Schematic diagram of the formation of the perovskite quantum dot glue provided in Example 1 after curing of the present invention. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] The materials used in the subsequent embodiments include:

[0046] Polyurethane acrylate: ZHU-2197 UV curing resin;

[0047] Fluorosilicone modified polyurethane acrylate: U-CURE 9313;

[0048] Diffusion particles: silicone light diffuser HL603.

[0049] Preparation Example 1

[0050] Perovskite quantum dots FAPbBr3

[0051] FAPbBr3 quantum dots were prepared using oleic acid ligands in combination with a traditional hot injection method. The specific steps included: weighing 0.416 g of formamidine acetate and 0.75 g of lead acetate into a reaction container, adding 5 mL of oleic acid and 50 mL of octadecene thereto, degassing at an appropriate temperature, passing nitrogen and heating to 120°C, adding 1.74 g of oleylamine bromide dissolved in toluene in advance, reacting for 5 seconds, and bathing in ice water to obtain a crude perovskite quantum dot solution; centrifuging the crude perovskite quantum dot solution with ethyl acetate and toluene to obtain a quantum dot purified solution, taking 10 mL of the purified liquid and centrifuging it with ethyl acetate to remove the remaining solvent to obtain a quantum dot precipitate, i.e., the perovskite quantum dot FAPbBr3 was obtained.

[0052] Preparation Example 2

[0053] Perovskite quantum dots CsPbBr3

[0054] The only difference between the preparation method and Preparation Example 1 is that, in the preparation method, 0.416 g of formamidine acetate is replaced by 0.215 g of cesium carbonate, and other raw materials, amounts and step parameters are the same as those in Preparation Example 1.

[0055] Example 1

[0056] The present embodiment provides a perovskite quantum dot glue, including 20g polyurethane acrylate, 2g diffusion particles, 100mg isobornyl acrylate, 100mg photoinitiator 1173, 200mg multifunctional ligand trimethylolpropane tris(3-mercaptopropionate) (TMMP) and 200mg quantum dots FAPbBr3; the mass ratio of the quantum dots to the multifunctional ligand is 1:1.

[0057] This embodiment provides a method for preparing perovskite quantum dot glue, which specifically includes the following steps:

[0058] According to the formula, polyurethane acrylate, diffusion particles, isobornyl acrylate, photoinitiator 1173 and multifunctional ligand trimethylolpropane tris(3-mercaptopropionate) are evenly mixed, and the obtained mixture is mixed with quantum dots FAPbBr3 for 30 minutes, and placed in a degassing machine for vacuum centrifugation for 5 minutes to obtain the perovskite quantum dot glue.

[0059] Example 2

[0060] The present embodiment provides a perovskite quantum dot glue, including 30g polyurethane acrylate, 4g diffusion particles, 500mg trimethylolpropane triacrylate, 200mg photoinitiator TPO, 400mg multifunctional ligand trimethylolpropane tris(3-mercaptopropionate) and 200mg quantum dots FAPbBr3; the mass ratio of the quantum dots to the multifunctional ligand is 1:2.

[0061] This embodiment provides a method for preparing perovskite quantum dot glue, which is different from Example 1 only in that, in the preparation method, the mixing time is 40 minutes, and the other steps are the same as those in Example 1.

[0062] Example 3

[0063] The present embodiment provides a perovskite quantum dot glue, including 35g of polyurethane acrylate, 3g of diffusion particles, 1000mg of isobornyl methacrylate, 300mg of photoinitiator 1173, 800mg of multifunctional ligand trimethylolpropane tris(3-mercaptopropionate) and 200mg of quantum dots FAPbBr3; the mass ratio of the quantum dots to the multifunctional ligand is 1:4.

[0064] This embodiment provides a method for preparing perovskite quantum dot glue, and the specific steps are the same as those in Example 1.

[0065] Example 4

[0066] This embodiment provides a perovskite quantum dot glue, which differs from Embodiment 1 only in that the polyurethane acrylate is replaced with an equal mass of fluorosilicone-modified polyurethane acrylate resin, and the other components, amounts and preparation methods are the same as those in Embodiment 1.

[0067] Example 5

[0068] This embodiment provides a perovskite quantum dot glue, which differs from Example 1 only in that the TMMP is replaced with an equal mass of 1,4-bis(3-mercaptobutyryloxy)butane (BDI), and the other components, amounts and preparation methods are the same as those in Example 1.

[0069] Example 6

[0070] This embodiment provides a perovskite quantum dot glue, which differs from Example 1 only in that the TMMP is replaced with an equal mass of pentaerythritol tetrakis(3-mercaptopropionate) (PEMP), and the other components, amounts and preparation methods are the same as those in Example 1.

[0071] Example 7

[0072] This embodiment provides a perovskite quantum dot glue, which is different from Example 1 only in that the perovskite quantum dots are the quantum dots CsPbBr3 provided in Preparation Example 2, and the other components, amounts and preparation methods are the same as those in Example 1.

[0073] Example 8

[0074] This embodiment provides a perovskite quantum dot glue, which is different from Example 1 only in that, in the preparation method of the perovskite quantum dot glue, the mixing time is 60 minutes, and the other components, amounts and preparation methods are the same as those in Example 1.

[0075] Example 9

[0076] This embodiment provides a perovskite quantum dot glue, which is different from Example 1 only in that the polyurethane acrylate is replaced by an acrylate resin, and the other components, amounts and preparation methods are the same as those in Example 1.

[0077] Example 10

[0078] This embodiment provides a perovskite quantum dot glue, which is different from Example 1 only in that the amount of the perovskite quantum dots remains unchanged, the multifunctional ligand TMMP is reduced to 10 mg, the mass ratio of the two is 1:0.05, and the other components, amounts and preparation methods are the same as those in Example 1.

[0079] Embodiment 11

[0080] This embodiment provides a perovskite quantum dot glue, which differs from Example 1 only in that the amount of the perovskite quantum dots remains unchanged, the multifunctional ligand TMMP is increased to 2500 mg, the mass ratio of the two is 1:12.5, and the other components, amounts and preparation methods are the same as those in Example 1.

[0081] Example 12

[0082] This embodiment provides a perovskite quantum dot glue, which differs from Example 1 only in that isobornyl acrylate is replaced by an equimolar amount of triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione; trimethylolpropane tris(3-mercaptopropionate) is replaced by an equimolar amount of pentaerythritol tetrakis(3-mercaptopropionate), and the other components, amounts and preparation methods are the same as those in Example 1.

[0083] Comparative Example 1

[0084] This comparative example provides a perovskite quantum dot glue, which is different from Example 1 only in that the perovskite quantum dot glue does not contain a multifunctional ligand, isobornyl acrylate and photoinitiator 1173 are each 200 mg, and other components, dosages and preparation methods are the same as those in Example 1.

[0085] Application Examples

[0086] A perovskite quantum dot optical film comprises a first water and oxygen barrier film (thickness 130 μm), a perovskite quantum dot glue layer (thickness 40 μm) and a second water and oxygen barrier film (thickness 130 μm) stacked in sequence; the material of the perovskite quantum dot glue layer comprises the perovskite quantum dot glue provided in Examples 1-12 and Comparative Example 1; the preparation method of the perovskite quantum dot optical film comprises:

[0087] Perovskite quantum dot glue is coated on the surface of the first water and oxygen barrier film, and the second water and oxygen barrier film is compounded, and the film is irradiated under 365nm, 2000W ultraviolet light for 1 minute for curing to obtain the perovskite quantum dot optical film.

[0088] Performance Testing

[0089] (1) Photoluminescence quantum yield of the film: tested using a fluorescence spectrometer, the test instrument model is FLS1000;

[0090] (2) Resistance to blue light aging: Use a blue light LED light panel with a wavelength between 450-455nm to irradiate the perovskite quantum dot optical film, and record the time it takes for the brightness to drop by 10% (T90);

[0091] (3) Resistance to dry heat aging: The perovskite quantum dot optical film was placed in a constant temperature box of model CF-100L-C, the temperature was set to 85°C, and the time taken for the brightness to drop by 10% (T90) was recorded.

[0092] The test results of the photoluminescence quantum yield of the films corresponding to the above embodiments and the time it takes for the brightness to drop to T90 after aging are shown in Table 1:

[0093] Table 1

[0094]

[0095] It can be seen from the above table that the perovskite quantum dot glue provided by the present invention is compounded with other components by multidentate thiol compounds to achieve synergistic effects, so that the perovskite quantum dot glue has good stability, good resistance to blue light and dry heat aging, and long service life.

[0096] It can be seen from Example 1, Examples 5-6 and Comparative Example 1 that different types of multifunctional ligands can improve the performance of glue to varying degrees.

[0097] From the comparison between Example 1 and Example 7, it can be seen that this system also has an optimization effect on CsPbBr3 series quantum dots.

[0098] It can be seen from Example 1 and Example 8 that a perovskite quantum dot glue with better performance can be obtained when the mixing time is within the preferred range.

[0099] It can be seen from Example 1, Example 4 and Example 9 that the use of a suitable resin in the system can obtain a perovskite quantum dot glue with better performance and stability.

[0100] It can be seen from Example 1 and Examples 10 to 11 that the mass ratio of the amount of perovskite quantum dots to the multifunctional ligand is not within the range defined by the present invention. If the amount of multifunctional ligand added is too small, although it has no obvious effect on the quantum yield, the blue light resistance and dry heat aging resistance are worse; if the amount of multifunctional ligand added is too much, the quantum yield of the membrane will be seriously affected, and the aging stability will be average.

[0101] It can be seen from Example 1, Example 12 and Comparative Example 1 that different types of polymerization monomers and different types of multifunctional ligands can improve the optical properties and aging properties of the membrane, but the combination corresponding to Example 12 has a worse effect in the system of the present invention, indicating that specific types of polymerization monomers and multifunctional ligands are compounded to achieve better performance.

[0102] In summary, the perovskite quantum dot glue provided by the present invention avoids the problems of conventional perovskite quantum dots with many surface defects and average optical properties. The addition of multifunctional ligands effectively reduces the surface defects of perovskite quantum dots and improves important optical properties of quantum dots such as photoluminescence quantum yield and half-peak width. At the same time, by compounding with other components such as resins and monomers, the crosslinking degree and curing degree of the glue are improved, and the stability of the glue is further improved. In addition, the multifunctional ligand has strong applicability, simple preparation process, low cost, and can realize industrial production.

[0103] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A perovskite quantum dot glue, characterized in that: The perovskite quantum dot glue comprises resin, perovskite quantum dots, multifunctional ligands, polymer monomers and initiators; The multifunctional ligand includes a multidentate thiol compound.

2. The perovskite quantum dot glue according to claim 1, characterized in that The multidentate mercapto compound includes any one of trimethylolpropane tris(3-mercaptopropionate), 3-mercaptopropionic acid-[2,4,6-trioxo-1,3,5-triazine-1,3,5(2H,4H,6H)-secondary]tri-2,1-ethylene glycol ester, tetrakis(3-mercaptopropionic acid) pentaerythritol ester, tetrakis(3-mercaptobutyric acid) pentaerythritol ester or 1,4-bis(3-mercaptobutyryloxy)butane; more preferably trimethylolpropane tris(3-mercaptopropionate).

3. The perovskite quantum dot glue according to claim 1 or 2, characterized in that: The mass ratio of the perovskite quantum dots to the multifunctional ligand is 1:(0.1-10).

4. The perovskite quantum dot glue according to any one of claims 1 to 3, characterized in that: The molecular formula of the perovskite quantum dot is ABCl x Br y I 3-x-y ; Wherein, A is selected from at least one of Cs, FA or MA; B is selected from Pb and / or Sn; 0≤x≤3,0≤y≤3; Preferably, the perovskite quantum dots include FAPbBr3 and / or CsPbBr3.

5. The perovskite quantum dot glue according to any one of claims 1 to 4, characterized in that: The resin includes at least one of acrylic resin, polyurethane resin, epoxy resin, silicone resin, polyurethane acrylic resin, fluorosilicone modified polyurethane acrylate resin, epoxy acrylic resin or polyester resin, and is more preferably polyurethane acrylic resin and / or fluorosilicone modified polyurethane acrylate resin; Preferably, the polymer monomer is a compound containing a carbon-carbon double bond; Preferably, the polymer monomers include propylene monomers and / or ethylene monomers; Preferably, the polymer monomer includes at least one of isobornyl acrylate, lauryl acrylate, n-butyl methacrylate, isooctyl methacrylate, isobornyl methacrylate, isodecyl methacrylate, lauryl methacrylate, hexanediol dimethacrylate, hexanediol diacrylate, trimethylolpropane triacrylate or styrene.

6. The perovskite quantum dot glue according to any one of claims 1 to 5, characterized in that: The initiator comprises a photoinitiator; Preferably, the perovskite quantum dot glue further comprises diffusion particles; Preferably, the diffusion particles include organic silicon compounds and / or inorganic oxides.

7. The perovskite quantum dot glue according to any one of claims 1 to 6, characterized in that: In parts by weight, the perovskite quantum dot glue comprises 10-40 parts of resin, 0.1-0.3 parts of perovskite quantum dots, 0.02-2 parts of multifunctional ligands, 0.02-2 parts of polymer monomers, 0.1-0.4 parts of initiators and 1-4 parts of diffusion particles.

8. A method for preparing the perovskite quantum dot glue according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The perovskite quantum dot glue comprises a resin, perovskite quantum dots, a multifunctional ligand, a polymer monomer and an initiator to obtain the perovskite glue; Preferably, the mixed material further comprises diffusion particles; Preferably, the mixing time is 10 to 60 minutes.

9. A perovskite quantum dot optical film, characterized in that: The perovskite quantum dot optical film comprises a base film and the perovskite quantum dot glue according to any one of claims 1 to 7.

10. A display module, characterized in that: The display module comprises the perovskite quantum dot glue according to any one of claims 1 to 7 and / or the perovskite quantum dot optical film according to claim 9.

Citation Information

Cited By

  • Blocking-layer-free flexible quantum dot film and preparation method thereof

    CN120239416A